THE INFLUENCE OF MARKETING MIX AND MARKETING ENVIRONMENT TOWARDS CUSTOMERS SATISFACTION TO ENHANCE THE LOCAL SMALL MEDIUM ENTERPRISES COMPETITIVE ADVANTAGE - Raditya Ardianwiliandri; Rio Prasetyo Lukodono; Remba Yanuar Efranto (JEMIS (Journal of Engineering & Management in Industrial System), 2021)
Fruit Chip is one of the most well known Small Medium Enterprise’s products in Batu Malang. This is due to the high number of fruit production produced in this city. In selling their products, local Small Medium Enterprise have to face the highly competition from other producers as well who also produced similar products. The increasing number of tourists who came into Batu City also encouraging local Small Medium Enterprises to capture this opportunity by producing food souvenirs such as fruit chip. Therefore, every local Small Medium Enterprises should make continuous improvements in all areas as well as improving the quality of their products especially to maintain and attract the consumers. One of the key areas that need to be developed is marketing by conducting marketing research. This marketing research is conducted by observing the marketing environment (X1) and marketing mix-7P’s (X2) towards the customer satisfaction (Y) using Structural Equation Modelling (SEM). Based on the regression analysis, we can conclude that there is significant correlation between marketing mix towards customer satisfaction. The most influential variable in marketing mix is employee, promotion, process, and places. While the biggest influence in marketing environment is new entrants and customer variables.